2023
DOI: 10.1002/cre2.716
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on the effect of silver diamine fluoride for management of dental caries in permanent teeth

Abstract: Objectives The objective of this review is to assess the available literature systematically related to the effect of silver diamine fluoride (SDF) for the management of occlusal and root carious lesions in permanent teeth regardless of age. Materials and Methods This systematic review was conducted according to the Cochrane Handbook for Systematic Reviews of Interventions and Preferred Reporting Items for Systematic Review and Meta‐Analyses statement. A literature sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Consistently with our results, a meta-analysis revealed that both SDF and CHX are clinically effective in reducing new root caries lesions compared to placebos, but with SDF showing a better effect than chlorhexidine [56]. SDF has shown higher preventive fractions, when compared to other topical applications like NaF varnish [21,22,57], even when tested in dependent or institutionalized elderly individuals [24]. However, other authors have not found significant differences between the use of fluoride varnish and SDF [58], not even when adding SDF to fluoride varnish in institutionalized elderly individuals compared to using fluoride varnish alone [59].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistently with our results, a meta-analysis revealed that both SDF and CHX are clinically effective in reducing new root caries lesions compared to placebos, but with SDF showing a better effect than chlorhexidine [56]. SDF has shown higher preventive fractions, when compared to other topical applications like NaF varnish [21,22,57], even when tested in dependent or institutionalized elderly individuals [24]. However, other authors have not found significant differences between the use of fluoride varnish and SDF [58], not even when adding SDF to fluoride varnish in institutionalized elderly individuals compared to using fluoride varnish alone [59].…”
Section: Discussionsupporting
confidence: 90%
“…During the last decade, silver diamine fluoride (SDF) has had a prominent role as an effective preventive method of dental caries, both in enamel caries [18][19][20][21][22], as on root lesions [23][24][25][26][27][28][29]. SDF is an alkaline topical solution that contains fluoride and silver [30].…”
Section: Introductionmentioning
confidence: 99%
“…These findings align with previous studies that have demonstrated the superiority of SDF in caries prevention and arrest, particularly in primary and permanent teeth. 33 , 34 …”
Section: Discussionmentioning
confidence: 99%
“…Originating in Japan in the 1960s, SDF's chemical composition, encompassing 25% silver for antimicrobial action, 8% ammonia as a solvent, and 5% fluoride for remineralization, underlines its versatility and therapeutic potential. Also, FDA clearance in 2014 further attests to its safety and efficacy, marking it as a valuable tool in pediatric dentistry 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Parental acceptance of SDF application on their children's teeth is a subject of growing interest within the field of pediatric dentistry 13 . SDF's clinical efficacy is well-documented, but its acceptance as a treatment option hinges on how parents perceive its outcomes.…”
Section: Introductionmentioning
confidence: 99%